2021
DOI: 10.1016/j.cattod.2020.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable catalytic activity of polymeric membranes containing gel-trapped palladium nanoparticles for hydrogenation reactions

Abstract: Remarkable catalytic activity of polymeric membranes containing gel-trapped palladium nanoparticles for hydrogenation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…TEM images of the 1.0 wt % Pd/PSf dope solution were observed on a Tecnai G2 F2O X-Twin MAT equipped with an energy dispersive X-ray spectrometer (EDS) to investigate the particle size, distribution and elemental composition of the polymer dope solution (Figure 3). PdNPs were evenly dispersed in the polymer dope solution with some aggregation which was reliant on the intensity of the polymer and Pd nanoparticles [27]. The small PdNPs of average size of 5 nm formed sparsely distributed clusters as observed in Figure 3 (a).…”
Section: Charaterisation Of the Membranesmentioning
confidence: 88%
“…TEM images of the 1.0 wt % Pd/PSf dope solution were observed on a Tecnai G2 F2O X-Twin MAT equipped with an energy dispersive X-ray spectrometer (EDS) to investigate the particle size, distribution and elemental composition of the polymer dope solution (Figure 3). PdNPs were evenly dispersed in the polymer dope solution with some aggregation which was reliant on the intensity of the polymer and Pd nanoparticles [27]. The small PdNPs of average size of 5 nm formed sparsely distributed clusters as observed in Figure 3 (a).…”
Section: Charaterisation Of the Membranesmentioning
confidence: 88%
“…For example, Pd NPs are good catalysts for various hydrogenation reactions because of their unique affinity to hydrogen. Several studies loaded Pd NPs onto PAA and poly(ionic liquid) grafted PES membrane surfaces through in-situ chemical reduction for catalytic reactions (Emin et al, 2014;Gu et al, 2015;López-Viveros et al, 2021). However, the catalytic activity of Pd nanoparticles may be reduced due to the coverage of biofoulants like proteins and polysaccharides during filtration process (Cheng et al, 2016).…”
Section: Other Metal and Metal Oxide Npsmentioning
confidence: 99%
“…As the liquid is forced to percolate through the porosity of the membranes, such as through in-capillary microcolumns, the catalytic reaction is forced to occur. A literature survey on the subject suggested that Pd NPs present a great interest for such preformed or home-made systems [ 27 , 63 , 65 ]. The design and application in heterogeneous supported catalysis applications of diverse polymer-based membranes exhibiting nanoporosity has also been reported in the literature.…”
Section: Structured Hybrid Materials For Catalyzing Molecular Reactionsmentioning
confidence: 99%